2015
DOI: 10.4103/2231-0762.151970
|View full text |Cite
|
Sign up to set email alerts
|

Mutans streptococci estimation in saliva before and after consumption of probiotic curd among school children

Abstract: Background:According to the World Health Organization, probiotics are live microorganisms which when administered in adequate amounts and confer a health benefit to the host. Use of probiotics in children to improve oral health may lead to non-pathogenic bacteria replacing cariogenic bacteria. Dairy foods like cheese, curd, and milk are considered useful vehicles for probiotic bacteria.Aim:To compare the levels of salivary mutans streptococci before and after consumption of probiotic curd.Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Studies have shown that the eff ect of pilocarpine on physiologic saliva secretion is not as strong as the eff ect of lemon juice [22] and yogurt [23]. Various studies have speculated the use of natural yogurt and probiotic yogurt against S. mutans in the prevention of dental caries [24][25][26] and in hyposalivation [23]. In this study, the effi cacy of natural yogurt on saliva secretion was investigated and compared with the eff ect of lemon juice.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the eff ect of pilocarpine on physiologic saliva secretion is not as strong as the eff ect of lemon juice [22] and yogurt [23]. Various studies have speculated the use of natural yogurt and probiotic yogurt against S. mutans in the prevention of dental caries [24][25][26] and in hyposalivation [23]. In this study, the effi cacy of natural yogurt on saliva secretion was investigated and compared with the eff ect of lemon juice.…”
Section: Introductionmentioning
confidence: 99%
“…22 In several studies, a reduction in the S. mutans count with the consumption of probiotic-containing dairy products or lozenges was significant. 23,24 Our study differs from previous research with respect to the design, choice of probiotic species and the carrier food, period when the probiotic food was consumed, and culture medium. In addition, the dairy products utilized in earlier studies did not contain glucose or sucrose, both of which are shown to increase the S. mutans count.…”
Section: Discussionmentioning
confidence: 91%
“… 10 Bacterial strains that have been tested for probiotic action in the oral cavity and in vitro against oral pathogens include lactobacilli species ( Lactobacillus acidophilus, L. rhamnosus GG, Lactobacillus johnsonii, Lactobacillus casei, L. rhamnosus, Lactobacillus gasseri, Lactobacillus reuter, Lactobacillus paracasei, Lactobacillus plantarum ), Bifidobacterium species ( Bifidobacterium bifidum, Bifidobacterium longum, Bifidobacterium infantis, Bifidobacterium animalis strain DN-173 010), and others ( Streptococcus salivarius, Weissella cibaria ). 15 Clinical studies by Näse et al, 13 Caglar et al, 29 Haukioja et al, 30 Cildir et al, 31 Jindal et al, 9 Harini and Anegundi, 11 Khanafari et al, 14 Saha et al, 32 and Chinnappa et al (2013), 33 have confirmed that probiotic lactobacilli can reduce the counts of S. mutans after ingestion of L. rhamnosus -GG, L. reuteri, L. plantarum , and lactobacilli mix of which L. rhamnosus and L. plantarum were found to have better antimicrobial efficacy against S. mutans 9 , 13 , 14 , 30 , 32 and hence it was decided to use the blend of pure strains of the probiotic bacteria L. rhamnosus (TSP-Lrh1) and L. plantarum (TSP-Lp1) for the formulation of probiotic mucoadhesive patch.…”
Section: Discussionmentioning
confidence: 99%
“…Ltd., Mysuru) was determined taking into consideration the literature available on the use of safe and effective strength of probiotic strains in children from a dental point of view which ranges from 10 5 to 10 9 with 10 9 being most effective. 3 , 9 , 11 , 13 15 …”
Section: Aterials and M Ethodsmentioning
confidence: 99%